2023
DOI: 10.1039/d3ob01109g
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical direct C–H mono and bis-chalcogenation of indolizine frameworks under oxidant-free conditions

Amreen Chouhan,
Kusum Ucheniya,
Lalit Yadav
et al.

Abstract: A sustainable electrochemical approach for site-selective C–H mono and bis-chalcogenation (sulfenylation or selenylation) of indolizine frameworks is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…However, the cross-coupling reaction could not be inhibited completely by the radical scavenger DPE (Scheme 7a), and multiple pathways may be involved in this transformation. Thus, the reaction between diphenyl disulfide 4a and molecular iodine could also occur to produce the intermediate 9, [60][61][62] which attacked 1a to form intermediate G. Finally the product 5aa was formed through deprotonation of G (path b) (Scheme 8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the cross-coupling reaction could not be inhibited completely by the radical scavenger DPE (Scheme 7a), and multiple pathways may be involved in this transformation. Thus, the reaction between diphenyl disulfide 4a and molecular iodine could also occur to produce the intermediate 9, [60][61][62] which attacked 1a to form intermediate G. Finally the product 5aa was formed through deprotonation of G (path b) (Scheme 8).…”
Section: Resultsmentioning
confidence: 99%
“…According to literatures, PhSI (9) could be generated in situ from the reaction of 4a and I 2 (Scheme 7d). [60][61][62] Then, addition of 1a to the above solution generated the product 5aa in 41% isolated yield. These experiments suggested that 8 and 9 might be the main intermediates in this reaction.…”
mentioning
confidence: 99%
“…Very recently, Badsara and coworkers established an electrochemical protocol for the direct C–H monochalcogenation of cyclohexenone/cycloheptenone-fused indolizines 97 and the dichalcogenation of aryl/carbonyl-substituted indolizines 91 with odorless dichalcogenides 33 or 39 (X = S, Se) under photocatalyst-, metal catalyst- and oxidant-free conditions (Scheme 32). 170 The reactions were performed in an undivided cell equipped with C(+)/Ni(−) electrodes using KI as the additive and n Bu 4 NPF 6 as the electrolyte. Compared with the monochalcogenation, the dichalcogenation required an increased amount of KI, dichalcogenides and an extended reaction time.…”
Section: Directing Group-free Selective C–h Mono-/dichalcogenation Or...mentioning
confidence: 99%
“…1–6 This approach is considered indispensable and has received tremendous attention from the synthetic community, as it provides an alternative to traditional methods, employing electricity as the reagent to drive chemical reactions instead of using toxic or hazardous oxidizing or reducing reagents; also, it would be feasible to start electro-organic transformations precisely by altering the applied electrode potential. 7 Consequently, significant progress has been made in electrochemically driven redox reactions, showing a noteworthy advancement in developing sustainable synthetic organic electrochemistry. 8–11 Additionally, reactive intermediates, like carbocations, carbanions, and radicals, can be easily produced under mild conditions ( i.e.…”
mentioning
confidence: 99%